QRS complex distortion (Grade 3 ischaemia) as a predictor of myocardial damage assessed by cardiac magnetic resonance imaging and clinical prognosis in patients with ST-elevation myocardial infarction - Rommel, Karl-Philipp (Eur Heart J Cardiovasc Imaging, 2016)
AIMS: Distortion of the terminal portion of the QRS complex (so-called Grade 3 ischaemia, G3I) has been associated with adverse outcomes in ST-elevation myocardial infarction (STEMI) populations. However, the correlation of G3I with infarct size and microvascular injury as defined by cardiac magnetic resonance (CMR) is not well defined. Aim of this study was to assess the relation of G3I with myocardial damage as assessed by CMR and clinical outcomes in STEMI patients. METHODS AND RESULTS: We analysed the ECGs of 572 consecutive STEMI patients regarding the presence or absence of G3I. CMR was performed within 1 week after infarction for comprehensive assessment of myocardial damage using a standardized protocol. The primary clinical endpoint was major adverse cardiac events (MACE) within 12 months after infarction. G3I was present in 186 (32%) patients. The presence of G3I was associated with larger infarct size (P = 0.01), the presence of late microvascular obstruction (P = 0.05), the presence of intramyocardial haemorrhage (P = 0.04), and impaired myocardial salvage (P = 0.01). G3I was associated with a higher incidence of MACE (P = 0.01) and was identified as an independent predictor of MACE in Cox regression analysis (HR 2.19; 95% CI 1.10 to 4.38, P = 0.03). CONCLUSION: This largest study to date correlating G3I on the admission ECG with CMR markers of myocardial damage demonstrates that G3I is significantly associated with infarct size, impaired myocardial salvage, and reperfusion injury in a reperfused STEMI population. Moreover, G3I was independently associated with MACE. CLINICALTRIALS.GOV: NCT00712101.